Un archipiélago cinemático: Chiloé en el imaginario fílmico chileno, 2000–2023. - Álvarez, Asunción Díaz; Ojeda, Jorge Pavez (Studies in Latin American Popular Culture, 2025)
Across the twenty-first century, Chilean cinema has produced dozens of films inspired by the literature, mythology, territory, and history of Chiloé's archipelagos in the seas of southern Chile. Based on a survey of thirty-nine fiction films (short, medium, and feature) produced between 2000 and 2023, we propose a critical analysis of this filmography, looking specifically at the cinematic territories (the modes of appearance of the archipelagic territory and its subjects in the landscape form of the national cinematic imaginary) and the cinema poetics (the affection-image and the time-image of the islands' narratives) of these movies. This characterization allows us to identify three expressions of what we call an "archipelagic cinema": (1) ethno-fiction or archipelagic realism, heir of the shamanic cinema of the Chilean/Chilote director Raúl Ruiz and the video art of Juan Downey, (2) mythological fiction-documentary (or mytho-documentary), which adopts and adapts the oral and written literature of the island imagination (myths, legends, icons), and (3) ficto-critic cinema, which addresses the archipelago as a place of crystallized visualization of various forms of violence (sexual, racial, colonial).